Analysis of the c3 (v = 0, 1) State on the Basis of the 3A Band System in the 12C16O, 13C16O, and 14C16O Molecules. - Hakalla, Rafał (Academic Press (Journal of Molecular Spectroscopy), 2001)
Six bands of the 3A system (c 3Π-a 3Π) in the CO molecule have been photographed as an emission spectra by the Geissler tube. The conventional technique of spectroscopy has been implemented. It was the first attempt to analyze the 1-3 band in the 13C16O molecule as well as the 1-2 band in the 12C16O molecule at high resolution. The Th lines were used as a standard along with the interferometric comparator equipped with a photoelectric scanning device. The 0-2 and 0-3 bands in 12C16O and the 0-3 band in 13C16O and 14C16O were reanalyzed. The total number of lines studied within the framework of this project amounts to 3071. Due to complicated and not totally described perturbations which appeared in the upper state c 3Π(v = 0, 1), the effective rovibronic structure constants for this state were calculated (for the first time in the case of v = 1 level in the 12C16O). Global merging of the rotational constants of the a 3Π(v = 0, 1, 2, 3) and c 3Π(v = 0, 1) levels in 13C16O, as well as a 3Π(v = 2, 3) and c 3Π(v = 0, 1) in 12C16O, made it possible to obtain c 3Π vibrational differences Δv1-0 = 1742.0944 (22) cm-1 in 13C16O as well as 1775.7665 (41) cm-1 in 12C16O for the first time. The so far unknown band origins of the 0-v″ and 1-v″ progressions of the 3A system in the molecules under consideration have also been determined. The first attempt to specify the equilibrium molecular constants for the c 3Π state, along with the new values for the a 3Π state, on the basis of the obtained values of merged rovibronic constants has been undertaken. The vibrational constants of the c 3Π state in the 13C16O molecule as well as in the 12C16O molecule were thus obtained for the first time. The 1-2 band of 12C16O and Dunham's isotopic relationship were implemented for that purpose. The analysis of anomalously small values of the centrifugal distortion constant D of the c 3Π state and the global character of perturbations in the observed isotopes of the CO molecule suggest homogeneous interaction between c 3Π(v = 0, 1) and the k 3Π state. Simultaneously, the analysis of the comparatively large values of the Λ-doubling parameter q and the analysis of the shifts of the term values caused by perturbations presuppose a significant influence of a heterogeneous nature of any of the 3Σ states (most probably the j 3Σ+ state) on the c 3Π(v = 0, 1) state. The article also presents the first attempt to calculate RKR potentials, r-centroids, and Franck-Condon factors for the 3A system. © 2001 Academic Press.
Keywords: High resolution molecular spectroscopy; carbon monoxide; 12C16O; 13C16O; 14C16O Molecules